Intersectional Strategies for Targeting Amacrine and Ganglion Cell Types in the Mouse Retina - Jo, Andrew; Xu, Jian; Deniz, Sercan; Cherian, Suraj; DeVries, Steven H.; Zhu, Yongling (Frontiers in Neural Circuits, 2018)
The mammalian retina harbors over 100 different cell types. To understand how retinal circuits work, it is essential to systematically access each type. A widely used approach for achieving targeted transgene expression exploits promoter-driven Cre lines. However, Cre expression in a given transgenic line in the retina and elsewhere in the brain is rarely confined to a single cell type, contributing ambiguity to the interpretation of results from broadly applied manipulations. To obtain unambiguous information about retinal processing, it is desirable to have strategies for further restricting transgene expression to a few or even to a single cell type. We employed an intersectional strategy based on a Cre/Flp double recombinase system to target amacrine and ganglion cell types in the inner retina. We analyzed expression patterns in seven Flp driver lines and then created combinational mouse lines by selective cross breeding with Cre driver lines. Breeding with Flp lines can routinely remove more than 90% of the cells in Cre drivers, leading to only a handful cell types, typically 2-3, remaining in the intersection. Cre/Flp combinational mouse lines enabled us identify and anatomically characterize retinal cell types with greater ease and demonstrated the feasibility of intersectional strategies in retinal research. In addition to the retina, we examined Flp expression in the lateral geniculate nucleus and superior colliculus. Our results establish a foundation for future application of intersectional strategies in the retina and retino-recipient regions.